RegX3 Activates whiB3 Under Acid Stress and Subverts Lysosomal Trafficking of Mycobacterium tuberculosis in a WhiB3-Dependent Manner - Mahatha, Amar Chandra; Mal, Soumya; Majumder, Debayan; Saha, Sudipto; Ghosh, Abhirupa; Basu, Joyoti; Kundu, Manikuntala (Frontiers in Microbiology, 2020)
Two-component systems (TCSs) are central to the ability of Mycobacterium tuberculosis to respond to stress. One such paired TCS is SenX3-RegX3, which responds to phosphate starvation. Here we show that RegX3 is required for M. tuberculosis to withstand low pH, one of the challenges encountered by the bacterium in the host environment, and that it activates the cytosolic redox sensor WhiB3 to launch an appropriate response to acid stress. We show that the whiB3 promoter of M. tuberculosis harbors a RegX3 binding motif. Electrophoretic mobility shift assays show that phosphorylated RegX3 (RegX3-P) (but not its unphosphorylated counterpart) binds to this motif, whereas a DNA binding mutant, RegX3(K204A) fails to do so. Mutation of the putative RegX3 binding motif on the whiB3 promoter, abrogates the binding of RegX3-P. The significance of this binding is established by demonstrating that the expression of whiB3 is significantly attenuated under phosphate starvation or under acid stress in the regX3-inactivated mutant (delta regX3). Green fluorescent protein (GFP) reporter assays further confirm the requirement of RegX3 for the activation of the whiB3 promoter. The compromised survival of delta-regX3 under acid stress and its increased trafficking to the lysosomal compartment are reversed upon complementation with either regX3 or whiB3, suggesting that RegX3 exerts its effects in a WhiB3-dependent manner. Finally, using an in vitro granuloma model, we show that granuloma formation is compromised in the absence of regX3, but restored upon complementation with either regX3 or whiB3. Our findings provide insight into an important role of RegX3 in the network that regulates the survival of M. tuberculosis under acid stress similar to that encountered in its intracellular niche. Our results argue strongly in favor of a role of the RegX3-WhiB3 axis in establishment of M. tuberculosis infection.